Therapeutic Potential of Menstrual Blood-Derived Stem Cell Transplantation for Intrauterine Adhesions - He, Yantao; Han, Yanhua; Ye, Yun (Frontiers in Surgery, 2022)
An increasing number of women experience intrauterine adhesion as a result of intrauterine operations, such as induced abortion, which can cause infertility, recurrent abortion and amenorrhea. Although some strategies have been applied clinically, such as hysteroscopy adhesiolysis of intrauterine adhesions, the results have not been promising. As regenerative medicine develops, research on menstrual blood-derived stem cell transplantation is increasing due to the properties of these cells, including self-renewal, differentiation, angiogenesis, anti-inflammation and immunomodulation. As a result, menstrual blood-derived stem cells may be an ideal cell source for the treatment of intrauterine adhesion. Excitingly, it has been reported that autologous menstrual blood stem cells could recovery injured endometrium and improve infertility in patients with refractory intrauterine adhesion. In this review, we discuss the possible potentail of menstrual blood-derived stem cell transplantation for intrauterine adhesion, including the antifibrosis, angiogenesis, anti-inflammation and immunoregulation properties of the cells, which brings hopes for clinical therapy.